Information needs of industries in Iligan City and vicinity a survey - Bañada, Leticia C.; Hidalgo, Namnama P.; Aquino, Leticia E. (Quezon City : Institute of Library Science, University of the Philippines, 1978)
This study aimed to find out the information needs, information sources and services which are meeting the needs of industries in Metro Iligan
One hundred-thirty questionnaires were distributed by the researcher to the managers, supervisors, laboratory analysts, and accountants from fifteen major industrial firms in Metro Iligan. Of the 130 questionnaires which were distributed, 104 were returned and analyzed. Information yielded by the questionnaire were supplemented by interviews with respondents
The study revealed that members of industries in Metro Iligan need materials from diverse disciplines. Many of their information needs pertain to their product interests, occupational interests, professions, hobbies, and recreational reading interests. They have a felt need for technical information. Their technical information needs are met through the use of technical handbooks and technical journals. They are partly meeting their information needs through the use of public, industrial, and academic libraries accessible to them. Members of industries in Metro Iligan find current awareness services most useful for their technical literature needs
On the whole, the findings of this study point out that the decision-making industrial personnel in Metro Iligan have a definite need for information
In view of the felt need for information among the decision-making industrial personnel in Metro Iligan, it is recommended that existing libraries in Iligan City be strengthened to meet these information needs
It is proposed that there be established an Industrial Information Center and Services, a university-managed and industry-sponsored special library to serve the industries in Metro Iligan. The Center shall provide various services including the production of Current Awareness Lists and Current Contents similar to those produced by the Industrial Information Department of the University of the Philippines Institute for Small-Scale Industries
Mimeographed
Vita
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Information needs--Philippines--Iligan City; Information services--Philippines--Iligan City; Research, Industrial--Philippines--Iligan City